ASSESSMENT OF EMPLOYMENT AND DEMOGRAPHIC DEVELOPMENT OF THE POPULATION OF UZBEKISTAN BASED ON A NON-TRADITIONAL APPROACH - Ismailov Akmal Makhsudovich (American Journals, 2024)
This article theoretically substantiates the primacy of interest in human activity. The application of the economic law of the primacy of interest in human labor activity is theoretically and methodologically substantiated and, based on the interest index, demographic issues in the Republic of Uzbekistan, indicators of economic activity and employment of the population are analytically studied. Scientific proposals and recommendations have also been developed to increase employment and labor resources in the economic development of the country.
Keywords: Interest, dominance of interest, interest index, demographic problems, economic activity of the population, employment, labor resources.